CYBER ATTACK DETECTION AND LOCALIZATION METHOD BASED ON ADAPTIVE HIERARCHICAL DETECTION FOR ACTIVE DISTRIBUTION SYSTEMS - A.Sneha Chaturya (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
CYBER ATTACK DETECTION AND LOCALIZATION METHOD BASED ON ADAPTIVE HIERARCHICAL DETECTION FOR ACTIVE DISTRIBUTION SYSTEMS